A new ZVT-PWM DC-DC converter - Bodur, H; Bakan, AF (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2002)
In this paper, a new active snubber cell that overcomes most of the drawbacks of the normal zero voltage transition-pulse width modulation (ZVT-PWM) converter is proposed to contrive a new family of ZVT-PWM converters. A converter with the proposed snubber cell can also operate at light load conditions. All of the semiconductor devices in this converter are turned on and off under exact or near zero voltage switching (ZVS) and/or zero current switching (ZCS). No additional voltage and current stresses on the main switch and main diode occur. Also, the auxiliary switch and auxiliary diodes are subjected to voltage and current values at allowable levels. Moreover, the converter has a simple structure, low cost, and ease of control. A ZVT-PWM boost converter equipped with the proposed snubber cell is analyzed in detail. The predicted operation principles and theoretical analysis of the presented converter are verified with a prototype of a 2 kW and 50 kHz PWM boost converter with insulated gate bipolar transistor (IGBT). In this study, a design procedure of the proposed active snubber cell is also presented. Additionally, at full output power in the proposed soft switching converter, the main switch loss is about 27% and the total circuit loss is about 36% of that in its counterpart hard switching converter, and so the overall efficiency, which is about 91% in the hard switching case, increases to about 97%.
Keywords: active snubber cells; soft switching; zero current switching; zero current transition; zero voltage switching; zero voltage transition; Engineering